ATP-Binding Cassette and Solute Carrier Transporters: Understanding Their Mechanisms and Drug Modulation Through Structural and Modeling Approaches - Ahmad Elbahnsi; Balint Dudas; Isabelle Callebaut; Alexandre Hinzpeter; Maria A. Miteva (Pharmaceuticals)
The ATP-binding cassette (ABC) and solute carrier (SLC) transporters play pivotal roles in cellular transport mechanisms, influencing a wide range of physiological processes and impacting various medical conditions. Recent advancements in structural biology and computational modeling have provided significant insights into their function and regulation. This review provides an overview of the current knowledge of human ABC and SLC transporters, emphasizing their structural and functional relationships, transport mechanisms, and the contribution of computational approaches to their understanding. Current challenges and promising future research and methodological directions are also discussed.